PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SD INPRES BORISALLO KECAMATAN PARANGLOE KABUPATEN GOWA - Tahir, Masdiana; Suhaenah, Asriani; Aminah, Aminah (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2019)
The village of Borisallo is a Development Partner Village of UMI in Gowa Regency. One of theeducational facilities is SD Inpres Borisallo where a school is a place of learning that can be athreat of disease transmission if it is not managed properly. Problems with children's healthbehavior are usually related to personal and environmental hygiene. By that, the planting of valuesof health behavior in elementary schools is an absolute necessity and an effort to realize